Dynamics of genomic H3K27me3 domains and role of EZH2 during pancreatic endocrine specification - Xu, Cheng-Ran; Li, Lin-Chen; Donahue, Greg; Ying, Lei; Zhang, Yu-Wei; Gadue, Paul; Zaret, Kenneth S (The EMBO journal, 2014)
Endoderm cells undergo sequential fate choices to generate insulin‐secreting beta cells. Ezh2 of the PRC2 complex, which generates H3K27me3, modulates the transition from endoderm to pancreas progenitors, but the role of Ezh2 and H3K27me3 in the next transition to endocrine progenitors is unknown. We isolated endoderm cells, pancreas progenitors, and endocrine progenitors from different staged mouse embryos and analyzed H3K27me3 genome‐wide. Unlike the decline in H3K27me3 domains reported during embryonic stem cell differentiation in vitro , we find that H3K27me3 domains increase in number during endocrine progenitor development in vivo . Genes that lose the H3K27me3 mark typically encode transcriptional regulators, including those for pro‐endocrine fates, whereas genes that acquire the mark typically are involved in cell biology and morphogenesis. Deletion of Ezh2 at the pancreas progenitor stage enhanced the production of endocrine progenitors and beta cells. Inhibition of EZH2 in embryonic pancreas explants and in human embryonic stem cell cultures increased endocrine progenitors in vitro . Our studies reveal distinct dynamics in H3K27me3 targets in vivo and a means to modulate beta cell development from stem cells. Synopsis The in vivo analysis of Ezh2‐dependent H3K27me3‐dynamics during pancreatic endocrine specification could instruct optimized ES cell differentiation for future therapeutic application. During pancreatic endocrine development in embryos, genes that gain H3K27me3 typically are involved in cell biology and morphogenesis, whereas genes that lose H3K27me3 are typically involved in developmental gene regulation. The gain in H3K27me3 domains observed in pancreas development in embryos differs from the decline in such domains reported for ES cell differentiation to pancreas progenitors in vitro . Genetic diminution of Ezh2 at the pancreas progenitor stage in embryos enhances the subsequent production of endocrine progenitors and beta cells. Inhibition of EZH2 at the endocrine progenitor induction stage in differentiating human ES cells increases the production of beta‐like cells in vitro . Graphical Abstract The in vivo analysis of Ezh2‐dependent H3K27me3‐dynamics during pancreatic endocrine specification could instruct optimized ES cell differentiation for future therapeutic application.